The role of information - Momi Dahan; Udi Nisan (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper exploits a quasi-natural experiment to study the role of information in determining take-up patterns of social benefits in a non-stigma environment. We find that take-up rate of households who have the incentive to search for information for a longer period of time is between 8 and 13 percentage points higher as compared to a control group of households. This result is robust to the inclusion of various household characteristics. Our finding provides strong empirical support for information as an important explanation for low take-up rates.
Keywords: I38; 330